Molecular Characterization and Cluster Analysis of Field Isolates of Avian Infectious Laryngotracheitis Virus from Argentina - Craig, María I.; Rojas, Maria F.; van der Ploeg, Claudia A.; Olivera, Valeria; Vagnozzi, Ariel E.; Perez, Andrés M.; König, Guido A. (Frontiers in Veterinary Science, 2017)
Avian Infectious Laryngotracheitis (ILT) is a worldwide infectious disease that causes important economic losses in the poultry industry. Although it is known that ILTV is present in Argentina, there is no information about the circulating strains. With the aim to characterize them, seven different genomic regions (Thymidine Kinase, glycoproteins D,G, B, C, and J, and infected cell polypeptide 4, ICP4)) were partially sequenced and compared between field samples. The gJ sequence resulted to be the most informative segment, it allowed the differentiation among field sample strains, and also, between wild and vaccine viruses. Specific changes in selected nucleotidic positions led to the definition of 5 distinct haplotypes. Tests for detection of clustering were run to test the null hypothesis that ILTV haplotypes were randomly distributed in time in Argentina and in space in the most densenly-populated poultry region of this country, Entre Rios. From this study it was possible to identify a 46 km radius cluster in which higher proportions of haplotypes 4 and 5 were observed, next to a provincial route in Entre Rios and a significant decline of haplotype 5 between 2009 and 2011. Results here provide an update on the molecular epidemiology of ILT in Argentina, including data on specific genome segments that may be used for rapid characterization of the virus in the field. Ultimately, results will contribute to the surveillance of ILT in the country.